Coastal ocean circulation during Hurricane Sandy. Issue 9 (5th September 2017) - Miles, Travis; Seroka, Greg; Glenn, Scott
Abstract: Hurricane Sandy (2012) was the second costliest tropical cyclone to impact the United States and resulted in numerous lives lost due to its high winds and catastrophic storm surges. Despite its impacts little research has been performed on the circulation on the continental shelf as Sandy made landfall. In this study, integrated ocean observing assets and regional ocean modeling were used to investigate the coastal ocean response to Sandy's large wind field. Sandy's unique cross‐shelf storm track, large size, and slow speed resulted in along‐shelf wind stress over the coastal ocean for nearly 48 h before the eye made landfall in southern New Jersey. Over the first inertial period (∼18 h), this along‐shelf wind stress drove onshore flow in the surface of the stratified continental shelf and initiated a two‐layer downwelling circulation. During the remaining storm forcing period a bottom Ekman layer developed and the bottom Cold Pool was rapidly advected offshore ∼70 km. This offshore advection removed the bottom Cold Pool from the majority of the shallow continental shelf and limited ahead‐of‐eye‐center sea surface temperature (SST) cooling, which has been observed in previous storms on the MAB such as Hurricane Irene (2011). This cross‐shelf advective process has not been observed previously on continental shelves during tropical cyclones and highlights the need for combined ocean observing systems and regional modeling in order to further understand the range of coastal ocean responses to tropical cyclones. Plain Language Summary: Hurricane Sandy (2012) was the second costliest tropical cyclone to impact the United States and resulted in numerous lives lost due to its high winds and catastrophic storm surges. Despite its impacts little research has been performed on the circulation of the coastal ocean as Sandy made landfall. In this study integrated ocean observing assets and regional ocean modeling were used to investigate the coastal ocean response to Sandy's large wind field. Sandy's unique cross‐shelf storm track, large size, and slow speed resulted in powerful alongshore winds over the coastal ocean for nearly 48 h before the eye made landfall in southern New Jersey. These winds transported cold bottom waters offshore and left the coastal ocean uniformly warm and mixed. This circulation pattern has not been observed previously during tropical cyclones and highlights the need for a continued focus on coastal ocean observing systems and numerical modeling during storm events. Key Points: Tropical cyclones can have a large impact on coastal ocean circulation Sandy was an extreme event that drastically altered the water column characteristics through cross‐shelf advective processes Integrated ocean observing systems and regional modeling are critical tools to resolve coastal ocean circulation in tropical cyclones